Employer Voices, Employer Demands, and Implications for Public Skills Development Policy Connecting the Labor and Education Sectors - Cunningham, Wendy V.; Villaseñor, Paula (Published by Oxford University Press on behalf of the World Bank, 2017)
Educators believe that they are adequately preparing youth for the labor market while at the same time employers lament the students' lack of skills. A possible source of the mismatch in perceptions is that employers and educators have different understandings of the types of skills valued in the labor market. Using economics and psychology literature to define four skills sets—socio-emotional, higher-order cognitive, basic cognitive, and technical—this paper reviews the literature that quantitatively measures employer skill demand, as reported in a preference survey. A sample of 27 studies reveals remarkable consistency across the world in the skills demanded by employers. While employers value all skill sets, there is a greater demand for socio-emotional skills and higher-order cognitive skills than for basic cognitive or technical skills. These results are robust across region, industry, occupation, and education level. Employers perceive that the greatest skills gaps are in socio-emotional and higher-order cognitive skills. These findings suggest the need to re-conceptualize the public sector's role in preparing children for a future labor market. Namely, technical training is not equivalent to job training; instead, a broad range of skills, many of which are best taught long before labor market entry, should be included in school curricula from the earliest ages. The skills most demanded by employers—higher-order cognitive skills and socio-emotional skills—are largely learned or refined in adolescence, arguing for a general education well into secondary school until these skills are formed. Finally, the public sector can provide programming and incentives to non-school actors, namely parents and employers, to encourage them to invest in the skills development process.